A Comparison Between Reduced and Intentionally Oxidized Metal Catalysts for Growth of Single‐Walled Carbon Nanotubes. Issue 12 (22nd July 2018) - Qian, Yang; An, Hua; Inoue, Taiki; Chiashi, Shohei; Xiang, Rong; Maruyama, Shigeo
Abstract : In this article, the authors report a detailed comparative study on the growth of single‐walled carbon nanotubes (SWNTs) from monometallic and its oxide (intentionally oxidized) catalysts. The difference and findings are summarized in the following three aspects. 1) High‐quality SWNTs are also grown from intentionally oxidized Co nanoparticles, but the yield of SWNTs significantly decreases, resulting in random network rather than vertically aligned SWNT arrays. 2) The authors clarify from in‐plane transmission electron microscopy that Co oxide nanoparticles grow SWNTs through an in situ reduction process, which means Co oxide becomes metallic Co after the introduction of ethanol; direct growth from an oxide phase is not observed. 3) Compared to the SWNTs grown by pre‐reduced catalysts, SWNTs grown from intentionally oxidized catalysts show narrower diameter distribution and smaller average diameter from Raman spectra. The strategy also shows similar results in the Ni catalysts. The findings are helpful to improve the controllability of SWNT diameter and morphology, as well as the reproducibility and robustness of CVD process. Abstract : In this article, the authors report a detailed comparative study on the growth of single‐walled carbon nanotubes (SWNTs) from monometallic and its oxide catalysts. High‐quality SWNTs can also grow from internationally oxidized catalysts, and the resulting SWNTs show narrower diameter distribution and smaller average diameter than those from metallic catalysts. An in situ reduction process on oxide catalysts is clarified by in‐plane transmission electron microscopy.